An Opinion Piece on #ChatGPT - What do Generative Artificial Intelligence Technologies Reveal about Responsible Tourism Education that We don’t Already Know? - Tham, Aaron; Ting, Hiram; Kumarusamy, Risidaxshinni (Turizam, 2024)
The purpose of this paper is to evaluate the value of ChatGPT in terms of its responses and depth of progressing responsible tourism education. It is one of the first attempts to ascertain how ChatGPT responds to human-led queries, and whether it can formulate innovative ideas to advance responsible tourism theories into educational curriculum and assessments in the future. An ’interview’ was conducted with ChatGPT to explore the chatbot’s responses to a series of questions related to responsible tourism education. The questions were informed by developments on the concept of responsible tourism, and to ascertain whether the chatbot can synthesise and generate radically innovative ideas to advance how the concept can be taught in the future. ChatGPT provided quick responses to ‘interview’ questions posed on its platform. It does engage with the conversation and can formulate preliminary insights to educate students on responsible tourism stakeholder engagement for women and minority groups, though it does not necessarily have the depth to explain how these stakeholders can be equipped to realise desired outcomes. In addition, the ideas emanating from ChatGPT appear rather obvious, with few radical or innovative outcomes to drive the educational landscape of responsible tourism forward.